2021
DOI: 10.1111/1756-2171.12373
|View full text |Cite
|
Sign up to set email alerts
|

Hospital competition and quality for non‐emergency patients in the English NHS

Abstract: We investigate the effect on the quality of three high‐volume non‐emergency treatments of a reform that relaxed restrictions on patient choice of hospital. We employ a quasi difference‐in‐difference strategy and use control functions allowing for patient selection into providers correlated with unobserved morbidity. Public hospitals facing more rivals reduced quality, increased waiting times, and reduced length of stay for hip and knee replacements. This is likely due to regulated prices implying larger losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…14 See Gowrisankaran and Town (1999) for a related discussion of the bias in estimates of hospital quality when there is unobserved selection on the basis of quality 15 For the details of this procedure, see Moscelli et al (2021) .…”
Section: Effect Of Competition On Waiting Time Inequalities Within Ho...mentioning
confidence: 99%
See 3 more Smart Citations
“…14 See Gowrisankaran and Town (1999) for a related discussion of the bias in estimates of hospital quality when there is unobserved selection on the basis of quality 15 For the details of this procedure, see Moscelli et al (2021) .…”
Section: Effect Of Competition On Waiting Time Inequalities Within Ho...mentioning
confidence: 99%
“…A more recent paper by Gaynor et al (2013) for a period when hospitals faced fixed prices tests, inter alia , whether, after the 2006 choice reforms, hospitals facing more a more competitive market structure and finds no effect of the choice reform on the proportion of patients waiting more than three months ( Gaynor et al, 2013 , footnote 16). As part of a study which focussed on quality as measured by emergency readmissions and mortality and did not examine inequity and inequality, Moscelli et al (2021) found that the choice reform increased mean waiting times and did so by more in hospitals exposed to less competition pre reform but did not examine the effect on inequality and inequity in waiting times.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results found that public hospitals facing more rivals had reduced quality, increased waiting times and reduced length of stay. They concluded that this is due to the regulated price reform [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%